Design of an Electronic Worksheet Using a Problem-Based Learning Approach Oriented to ESD: Application of Buffer Concepts in the Cheese Industry to Train Students’ Scientific Literacy - Nazwa Nur Afifah; Hernani; Asep Supriatna (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Students’ science literacy in Indonesia remains relatively low and needs to be improved through contextual and meaningful learning. One approach that can be taken is to integrate Problem-Based Learning (PBL) and Education for Sustainable Development (ESD) into interactive teaching materials. This study aims to develop PBL-based e-worksheets integrated with ESD on the topic of buffer systems within the context of the cheese industry to enhance students’ science literacy. The method used is Design and Development Research (DDR), which includes the planning, production, and evaluation stages. The planning stage was conducted through a need analysis involving high school chemistry teachers, while the production stage involved the design and development of the e-worksheet, which was then validated by two lecturers and two chemistry teachers. The evaluation stage was conducted through a pilot test with 30 11th-grade high school students. The research results indicate that the developed e-worksheet possesses excellent quality, with a 100% feasibility rate across all evaluation aspects. Pilot test results show that students’ science literacy falls within the good to excellent categories, particularly regarding the ability to organize information, analyze data, and connect concepts to sustainability issues such as the SDGs and the circular economy. However, their ability to formulate problems and engage in deep scientific reasoning still needs improvement. Thus, this e-worksheet is deemed suitable for use and can foster science literacy through contextual, interactive, and sustainability-oriented learning.